World Bank Corporate Scorecard, April 2012 : Integrated Results and Performance Framework - World Bank (Washington, DC, 2017)
The corporate scorecard is designed to provide a snapshot of the Bank's overall performance, including its business modernization, in the context of development results. It facilitates strategic dialogue between management and the Board on progress made and areas that need attention. With the results measurement system, which was adopted for the 13th replenishment of the International Development Association (IDA13) in 2002, the Bank became the first multilateral development institution to use a framework with quantitative indicators to monitor results and performance. The corporate scorecard expands this approach to the entire World Bank covering both the International Bank for Reconstruction and Development (IBRD) and IDA. The corporate scorecard uses an integrated results and performance framework, which is organized in a four-tier structure that groups indicators along the results chain. Tier one is development context. Tier two is development results supported by the Bank. Whether the Bank is managing its operations and services effectively is shown in tier three. Tier four focuses on whether the Bank is managing skills, capacity, resources, and processes efficiently; and is business modernization on track?